2009
DOI: 10.1111/j.1556-4029.2008.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparison of Electrical Tapes Using Instrumental and Statistical Techniques: II. Organic Composition of the Tape Backing and Adhesive*

Abstract: The microtexture and elemental composition of the backing of electrical tapes have been shown to be highly discriminating. In this study, the organic composition of electrical tape was evaluated as a complementary means of distinguishing tape brands. The backing and adhesive of 72 rolls of electrical tape were analyzed via Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR FTIR) and discriminant analysis was used to classify all samples by brand. Generally, the accuracy for FTIR data (88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Also at http://dx.doi.org/10.1016/j.scijus.2009.08.001 p2 tapes available; composition varies with manufacturer, brand and batch, for example glues used in adhesive tapes may be based on acrylate or natural or synthetic rubber. Tapes of different sources can be distinguished by laboratory methods such as Fourier-transform infra-red analysis (FTIR) [11,13]. Development success rates and comparative effectiveness of print development from different formulations do vary with type of adhesive tape studied, as shown by both Brzozowski [10] and Richardson [11], in their comprehensive studies of development efficacy of various power suspensions in depletion series on commercial tapes.…”
Section: Introductionmentioning
confidence: 99%
“…Also at http://dx.doi.org/10.1016/j.scijus.2009.08.001 p2 tapes available; composition varies with manufacturer, brand and batch, for example glues used in adhesive tapes may be based on acrylate or natural or synthetic rubber. Tapes of different sources can be distinguished by laboratory methods such as Fourier-transform infra-red analysis (FTIR) [11,13]. Development success rates and comparative effectiveness of print development from different formulations do vary with type of adhesive tape studied, as shown by both Brzozowski [10] and Richardson [11], in their comprehensive studies of development efficacy of various power suspensions in depletion series on commercial tapes.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, forensic scientists are requested to compare fragments of a tape encountered at a crime scene with fragments originated from a suspect in order to establish whether they could come from the same roll (have a common origin). Visual investigations performed currently provide information about physical fit, tape width, colour and morphology [1]. Infrared spectroscopy (FT-IR) and pyrolysis gas chromatography (Py-GC-MS) enable characterisation of organic compounds in the backing layer and adhesive layer of the tape [2][3][4] and Inductively Coupled Plasma Mass Spectrometry (ICP/MS) points to their elemental composition [5,6] as well as X-ray fluorescence spectroscopy (XRF) [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since publication of this report, there has been increasing interest in applying multivariate statistical procedures to forensically relevant chromatographic and spectral data. For example, principal components analysis (PCA), cluster analysis, and discriminant analysis have been applied in the analysis of fire debris [2][3][4][5], explosives [6], controlled substances [7][8][9], and various trace evidence types including hair [10], soil [11], electrical tape [12], and paint [13][14][15]. Forensic research in this area has conclusively demonstrated the potential of these procedures for case work.…”
Section: Introductionmentioning
confidence: 98%